2011
DOI: 10.1007/s10653-011-9381-7
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated lead environments of man: reviewing the lead isotopic evidence in sediments, peat, and soils for the temporal and spatial patterns of atmospheric lead pollution in Sweden

Abstract: Clair Patterson and colleagues demonstrated already four decades ago that the lead cycle was greatly altered on a global scale by humans. Moreover, this change occurred long before the implementation of monitoring programs designed to study lead and other trace metals. Patterson and colleagues also developed stable lead isotope analyses as a tool to differentiate between natural and pollution-derived lead. Since then, stable isotope analyses of sediment, peat, herbaria collections, soils, and forest plants hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 116 publications
3
26
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The Pb is certainly the most powerful among radiogenic elements available with respect to isotope geochemists, because it has three radiogenic isotopes whose precursors of U and Th are relatively short half-lives and are very different from each other, and the chemistry of Pb is also quite different from that of its precursors. Laser ablation multi-collector inductively coupled plasma mass spectrometry (LA-MC-ICPMS) has already been accepted as a suitable tool for precise isotopic microanalysis in solid samples at scales down to about 5 -100 μm; since the MC-ICPMS can achieve simultaneous multi-isotope measurements by its multi-collector even though the number of detector is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The Pb is certainly the most powerful among radiogenic elements available with respect to isotope geochemists, because it has three radiogenic isotopes whose precursors of U and Th are relatively short half-lives and are very different from each other, and the chemistry of Pb is also quite different from that of its precursors. Laser ablation multi-collector inductively coupled plasma mass spectrometry (LA-MC-ICPMS) has already been accepted as a suitable tool for precise isotopic microanalysis in solid samples at scales down to about 5 -100 μm; since the MC-ICPMS can achieve simultaneous multi-isotope measurements by its multi-collector even though the number of detector is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, the Pb burden from all emissions to present stands at 2-5 g/m 2 in the south and 1 g/m 2 in the more remote north (Bindler, 2011). For the Southern Hemisphere, enrichment is less well constrained but is presently lower due to lower volume of industrial emissions.…”
Section: Peat and Ice Records Of The Atmospheric Depositionmentioning
confidence: 99%
“…Beginning in prehistoric times, human activities have modified the flux of metals to the extent that anthropogenic metals can now be considered ubiquitous in the Earth's environment (Bindler, 2011;Murozumi et al, 1969;Shotyk, 1996a). Patterson et al (1965) demonstrated the scale of their impact when they showed in the 1960s that blood Pb concentrations in the United States of America had reached approximately 100 times natural levels.…”
Section: Atmospheric Industrial Metals In the Earth's Environmentmentioning
confidence: 99%
See 2 more Smart Citations